Forget me not : a novel - Oliva, Alexandra (Ballantine Books, 2021)
Abandoned by a grieving mother to raise herself in a walled-off property in rural Washington, Linda escapes into a hostile outside world before a potential friendship and an unexplained fire unleash life-threatening consequences.